Analysis of the epidemiological profile of Leishmaniasis cases in Teresina between 2017 and 2019 (Research, Society and Development, 2022)
Introduction: The objective of this work is to evaluate the epidemiological profile of VL and ACL cases in the capital of Piauí in the years 2017 to 2019. Methods: This is a descriptive, retrospective study with a quantitative approach, carried out from secondary data collected in the database of the National System of Notifiable Diseases (SINAN) available on electronic platforms through the Department of Informatics of the Unified Health System. (SINAN). DATASUS). The factors evaluated were: sex, age group, color/race and evolution. Results: 474 cases of Visceral Leishmaniasis (VL) and 62 cases of American Cutaneous Leishmaniasis (ACL) were reported in the place and period studied. There was a greater number of cases in the male population, 328 cases of VL (69.19%) and 45 cases of ACL (72.58%). Regarding race/color, brown color predominated, with percentages of 87.13% for LV and 67.74% for ACL. According to age group, it was found that cases of ACL are predominant in the adult population, corresponding to about 64.51% of reported cases. For VL, the most affected age groups were between 20 and 39 years old, with 118 cases and between 1 and 4 years old, with a total of 103 registered cases. According to the clinical evolution, both VL and ACL, the Ignored/White cases stood out. Conclusion: According to socioeconomic studies, the Brazilian active workforce is mostly composed of brown/black men, so these individuals are more exposed to the vectors of Leishmania, justifying the profile found in the research.